Ceramide inhibitor myriocin restores insulin/insulin growth factor signaling for liver remodeling in experimental alcohol‐related steatohepatitis. Issue 10 (23rd September 2013) - Lizarazo, Diana; Zabala, Valerie; Tong, Ming; Longato, Lisa; de la Monte, Suzanne M.
Abstract: Background and Aim: Alcohol‐related liver disease (ALD) is mediated in part by insulin resistance. Attendant dysregulation of lipid metabolism increases accumulation of hepatic ceramides that worsen insulin resistance and compromise the structural and functional integrity of the liver. Insulin and insulin growth factor (IGF) stimulate aspartyl‐asparaginyl‐β‐hydroxylase (AAH), which promotes cell motility needed for structural maintenance and remodeling of the liver. AAH mediates its effects by activating Notch, and in ALD, insulin/IGF signaling, AAH, and Notch are inhibited. Method: To test the hypothesis that in ALD, hepatic ceramide load contributes to impairments in insulin, AAH, and Notch signaling, control and chronic ethanol‐fed adult Long–Evans rats were treated with myriocin, an inhibitor of serine palmitoyl transferase. Livers were used to assess steatohepatitis, insulin/IGF pathway activation, and expression of AAH–Notch signaling molecules. Results: Chronic ethanol‐fed rats had steatohepatitis with increased ceramide levels; impairments in signaling through the insulin receptor, insulin receptor substrate, and Akt; and decreased expression of AAH, Notch, Jagged, Hairy–Enhancer of Split‐1, hypoxia‐inducible factor 1α, and proliferating cell nuclear antigen. Myriocin abrogated many of these adverse effects of ethanol, particularly hepatic ceramide accumulation, steatohepatitis, and impairments of insulin signaling through Akt, AAH, and Notch. Conclusions: In ALD, the histopathology and impairments in insulin/IGF responsiveness can be substantially resolved by ceramide inhibitor treatments, even in the context of continued chronic ethanol exposure.